Adsorption behavior of biochar pyrolyzed from barracuda grass for cadmium ions - Shao, Yan; Chen, Zhiliang; Zhang, Zhonglei; Pang, Jun; Li, Yinyin; Zhu, Jia; Zhang, Gen; Wang, Xiaoshu; Chang, Ming; Wang, Lei (Frontiers in Chemistry, 2022)
This work investigated the removal of cadmium ions (Cd2+) by using biochar derived from Barracuda Grass. The biochars derived from the pyrolysis of roots (BGR), stems (BGS) and leaves (BGL) were characterized and their performance for cadmium adsorption was studied at varying parameters of temperature, time, and alkali (earth) metal concentrations. The maximum adsorption amount at the equilibrium of BGR, BGS, and BGL was determined experimentally as 8.38mg/g, 42.12mg/g, and 30.39mg/g. Adsorption fitting results revealed that Cd2+ adsorbed on BGR and BGS preferred to be multilayer-covered, and BGL was more likely to have monolayer-covered functions. The kinetic data fitted well to the pseudo-second-order model (R2>0.99), revealing the adsorption process was a spontaneous monolayer chemisorption process. The results of alkaline (earth) metals leaching of biochar revealed that the inherent alkaline (earth) metals in biochar made inhibitory functions on the Cd2+ adsorption behavior by occupying the active sites. And in the process of wastewater treatment, the leaching of alkaline earth metals might enhance the complexation reaction between surface groups and Cd2+. This study provides a feasible strategy for the resource utilization of abundant hydrophytic plants in waste management.